2020
DOI: 10.1007/s12369-020-00634-z
|View full text |Cite
|
Sign up to set email alerts
|

Assistive Robots for the Social Management of Health: A Framework for Robot Design and Human–Robot Interaction Research

Abstract: There is a close connection between health and the quality of ones social life. Strong social bonds are essential for health and wellbeing, but often health conditions can detrimentally affect a persons ability to interact with others. This can become a vicious cycle resulting in further decline in health. For this reason, the social management of health is an important aspect of healthcare. We propose that socially assistive robots (SARs) could help people with health conditions maintain positive social lives… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 77 publications
0
20
0
Order By: Relevance
“…The models created will help the robot to interact with the patient both verbally and nonverbally [ 34 ]. In a recent study [ 35 ], the authors have reported the development of a socially assistive robot that enables people to maintain not only their health condition but also support them during social interaction. The designed robot can help the patients to improve their perception ability, social behavior, and provide structure for interaction.…”
Section: Definition Architecture and Basic Functionalities Of Iot-aided Robotic Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The models created will help the robot to interact with the patient both verbally and nonverbally [ 34 ]. In a recent study [ 35 ], the authors have reported the development of a socially assistive robot that enables people to maintain not only their health condition but also support them during social interaction. The designed robot can help the patients to improve their perception ability, social behavior, and provide structure for interaction.…”
Section: Definition Architecture and Basic Functionalities Of Iot-aided Robotic Systemmentioning
confidence: 99%
“…The designed robot can help the patients to improve their perception ability, social behavior, and provide structure for interaction. Furthermore, it can also change the feeling of a person [ 35 ]. Sharif and Alsibai have developed a “Nao Robot” that can analyze the medical data and interact with patients.…”
Section: Definition Architecture and Basic Functionalities Of Iot-aided Robotic Systemmentioning
confidence: 99%
“…HRI studies of robots intervening in human-human interactions vary widely in their scope, and are scattered across domains of application, using very different robot designs in various contexts. However, some of these studies were conducted in lab settings while others were in more naturalistic settings such as nursing homes [27].…”
Section: Review Of Literaturementioning
confidence: 99%
“…These prospects raise several related but different questions. One is the empirical question of the technological and practical possibilities of care robots and their effects on human beings, as investigated in fields like social robotics and human–robot interaction (HRI) [ 2 7 ]. Another concerns the social and ethical dangers and benefits of robots, particularly ones that increasingly resemble humans, undertaking care work [ 8 18 ].…”
Section: Introductionmentioning
confidence: 99%